Penerapan Akuntansi PPN dan pengaruhnya terhadap aporan Keuangan di PT Grande Family view Proyek Manajemen Property Graha Family Surabaya - waryanto, r. bambang dwi (Fakultas Ekonomi Universitas PGRI Adi Buana, 2013)
Taxation is a source of state revenue that could be used to finance expenditures-spending, so the government is trying to maximize tax economic activities undertaken by the company. Every transaction of the goods and services that are performed by PT Grande Family View Property Management Graha Famili Surabaya, subject to Value Added Tax (VAT). In fulfilling their tax obligations, the company must do bookkeeping or VAT accounting in accordance with Financial Accounting Standards (IFRSs). The difference between time of the delivery of the Goods and Services with Tax invoicing cause differences in the recognition of expenses and debt based on GAAP and Tax Law. Therefore VAT accounting is essential to optimize the control function as a part of the VAT management conducted by PT Grande Family View to determine the amount of taxable income payable. This research aims to determine whether the company has implemented a VAT accounting and how it affect the company's financial statements among 2011th. The analysis technique used is to use the method of descriptive analysis with qualitative and quantitative data. The results showed that PT. Grande Family View Property Management Graha Famili Surabaya did not fully apply accounting in accordance with GAAP because the burden of VAT is not charged properly in accordance with GAAP, it caused the financial statements presented does not display accurate information about the company's true financial condition.